PERLINDUNGAN HUKUM TERHADAP KORBAN TINDAK PIDANA PENIPUAN MELALUI INTERNET - Dhaniar Eka Budiastanti (Jurnal Cakrawala Hukum, 2017)
The development of technology in addition to bringing positive impact, in its development also bring negative impact. The crime of using the internet as a means of committing crimes has increased substantially in the State of Indonesia as a form of negative impact. The Internet is used as a means to commit a crime, one of which is fraud. The protection granted by the Law of the Republic of Indonesia Number 19 the Year 2016 on Information and Electronic Transactions in the form of settlement of cases and the provision of criminal sanctions provided to the suspect or defendant. Article 28 paragraph (1) of the Law of the Republic of Indonesia Number 19 the Year 2016 on Information and Electronic Transactions may indicate as the article regulating fraud, but if examined more deeply, the elements contained in Article 28 paragraph (1) Law -The Republic of Indonesia No. 19 of 2016 on Information and Electronic Transactions is still considered less to meet the elements contained in the act that provides fictitious information in terms of sales of goods in cyberspace. Another case with Article 378 of the Criminal Code, which detailed parse elements of acts that provide fictitious information.